Isolasi dan Ekstraksi Kelompok Senyawa Flavonoid dari Ekstrak Daun Cocor Bebek (Kalanchoe pinnata) - Atikah Halimah Putri; Ria Siti Putriyana; Novia Silviani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Abstract Cocor bebek plant contains secondary metabolites which are useful in the field of pharmacology. This experiment aims to isolate flavonoid compounds which are secondary metabolites in cocor bebek. The extraction method uses maceration with methanol solvents, followed by partitions using ethyl acetate solvents. Identification of flavanoid group compounds was analyzed qualitative testing using FTIR and Thin Layer Chromatography (TLC) with the mobile phase of ethyl acetate : n-hexane with a ratio of 8:2, 7:3, 5:5, 3:7, and 2:8. The experimental results obtained from 600 grams of fresh cocor bebek leaves producing 3 gram of flavonoid extract. The qualitative test gave positive results for the TLC method the presence of flavonoids in the leaves of cocor bebek on spot yellow. While the levels of flavonoids in the extract of cocor bebek are obtained 4.20 ppm. Keywords: Cocor Bebek (Kalanchoe pinnata), Extraction, Flavonoids, Thin layer chromatography